An Overview of The Understanding and Attitudes of Food Handlers’ Hygiene and Sanitation in The Nutrition Installation of RSUD Dr. Pirngadi Medan - Nurhayati, Nurhayati; Gianing, Dwene Nur; Farhani, Nurhafiza; Lubis, Widya Hestina; Sari, Febi Nabila; Azzahra, Annastasya; Lubis, Anggi Khalisya Putri; Anggraini, Intan Nuryana; Haq, Zahara Dhiya'ul Haq Dhiya'ul; Hanin, Zhafirah (Universitas Teuku Umar, 2023)
The provision of hygienic and healthy food is the basic principle hospital food services are provided for patients who are very vulnerable to transmission of pathogenic germs. This analysis aims to illustrate the knowledge and attitudes of food handlers’ hygiene and sanitation at the Nutrition Installation of RSUD DR. Pirngadi Medan. This study used a cross-sectional approach to 20 food handlers on the morning shift at the nutrition installation at RSUD Dr. Pirngadi Medan. The result showed that the knowledge of food handlers at the Regional General Hospital Dr. Pirngadi Medan is included in the good category 75% and 85% bad category hygiene behavior. Results of data analysis obtained that there is no relationship between knowledge and hygiene and sanitation attitudes of food handlers.Based on the results of research that has been conducted at RSUD Dr. Pirngadi Medan still lacks awareness in the attitude of implementing hygiene and sanitation, such as often removing the mask when handling food due to the lack of a body to sweat quickly